DIGITAL TRANSFORMATION AND EFFECTIVE COMMUNICATION: THE PILLARS OF PRUCTIONAL SUCCESS AT MAN INSAN CENDEKIA PASER - Arbain, Arbain; Fajri, Muhamad; Susmiyati, Sri; Al Anshori, Habib Anwar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Effective communication is an essential element in successful public relations (PR) in educational institutions. This research aims to explore the effective communication strategies implemented by Public Relations at MAN Insan Scholar Paser in supporting the achievement of institutional goals. The research method used is qualitative with a case study approach. Data collection was carried out through in-depth interviews, observation and document analysis. The research results show that effective communication is created through the integration of modern communication technology, increasing interpersonal communication competence, and transparent information management. The conclusions of this research emphasize the important role of effective communication in strengthening the image of the institution and strengthening relationships with internal and external stakeholders